Pengaruh Model Make a Macht Terhadap Hasil belajar Kognitif Pemahaman Penerapan dan Penalaran Siswa Kelas V Materi IPA - Febria Kwartati; irwan koto (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2021)
This study aims to determine the effect of the model make a match on cognitive learning outcomes at the level of understanding, the application of fifth grade students of Natural Sciences in MI Al-Islam Bengkulu. This research is a quantitative descriptive study and a quasi experimental design experimental method. The population of this research is 83 students of MI Al-Islam Bengkulu City. The sample of this study was VA and VB classes, amounting to 59 students. Techniques in collecting data in this study are tests (pretest and posttest). Cognitive Ability Understanding the results of the U value is 0.017 <0.05 and Sig. (2-tailed) is 0.003 <0.05, so H01 is rejected Ha1 is accepted. Cognitive Ability Application of the U value is 0.025 <0.05 and Sig. (2-tailed) is 0.005 <0.05, so ?H? _02 is rejected Ha2 is accepted. Cognitive Ability Reasoning results U value is 0.027 <0.05 and Sig. (2-tailed) is 0,000 <0.05 then ?H? _03 is rejected Ha3 is accepted. In the results of hypothesis testing on the pretest and posttest values, it was concluded that there was a significant influence on the use of the Make a match model on the cognitive ability of reasoning in the learning of science class V SD in MI Al-Islam Bengkulu City.